2005
DOI: 10.1152/ajpcell.00215.2004
|View full text |Cite
|
Sign up to set email alerts
|

Are second messengers crucial for opening the pore associated with P2X7 receptor?

Abstract: Stimulation of the P2X7 receptor by ATP induces cell membrane depolarization, increase in intracellular Ca2+ concentration, and, in most cases, permeabilization of the cell membrane to molecules up to 900 Da. After the activation of P2X7, at least two phenomena occur: the opening of low-conductance (8 pS) cationic channels and pore formation. At least two conflicting hypotheses have been postulated to reconcile these findings: 1) the P2X7 pore is formed as a result of gradual permeability increase (dilation) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 58 publications
8
115
4
Order By: Relevance
“…Altogether, our data indicate that the pore formed by ionomycin has conductance, permeability, and cutoff similar to a pore induced by ATP (16,28). To test whether ionomycin-induced pore is the same pore formed by P2X 7 receptor, ionomycin was applied in the presence of different blockers of the P2X 7 receptor.…”
Section: Phospholipase C Inhibitors Blocked Ionomycin-induced Pore Fomentioning
confidence: 71%
See 3 more Smart Citations
“…Altogether, our data indicate that the pore formed by ionomycin has conductance, permeability, and cutoff similar to a pore induced by ATP (16,28). To test whether ionomycin-induced pore is the same pore formed by P2X 7 receptor, ionomycin was applied in the presence of different blockers of the P2X 7 receptor.…”
Section: Phospholipase C Inhibitors Blocked Ionomycin-induced Pore Fomentioning
confidence: 71%
“…Ferrari and colleagues (31) showed that polimixin B, which is a natural peptide used as an antibiotic, potentializes ATP effects in the membrane permeabilization and cytotoxic effects induced by extracellular Ca 2ϩ influx mediated by P2X 7 receptor. Recently, Faria and colleagues (28) demonstrated that the ATP-induced pore can be potentialized by Ca 2ϩ ionophores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…p38 MAPK and caspase inhibitors have been reported to impair P2X7-induced pore formation [33,34]. To exclude the possibility that the above compounds impaired P2X7-induced apoptosis of MEL cells by directly inhibiting P2X7, cells were pre-incubated in the presence of DMSO, SB202190, SB203580 or Z-VAD-FMK (as above), and the P2X7-induced ethidium + uptake assessed.…”
Section: P2x7-induced Ros Formation Is Impaired In Mel Cells Inmentioning
confidence: 99%